Technology University:Shifting from the Wrong Concepts to the Right Philosophy - Waghodekar, P. H. (Journal of Engineering Education Transformations, 2010)
This paper presents the need of establishing a large number of corporate-culture based Technology (Technical) Universities in India. The paper briefly takes an overview of philosophies related with education and university. Aims and objectives of education and university like transforming man in to a total human being, national prosperity, etc., are discussed. An account of ancient Indian universities and universities before and after independence is presented. The challenges before the Indian university education system are also presented and the efforts made to overcome these are briefly discussed. On taking an overview of the history of development of Technical and Management education in India, the functioning of some Technical Universities abroad is highlighted. And need of shifting Technical University based on the concepts of conventional university, to the right philosophy based on national interest is discussed. Present universities do not generate autonomous learners but, it is pointed out, these have remained the glorious high schools. A few recommendations, like, run university as corporate, global talent search. PBL approach, R&D emphasis, tenure for faculty, recruitment criteria, Process and Performance Management model, no tuition fees, degrees as "social" goods, etc., are made. The paper, it is believed, will of interest to all concerned.